PENGATURAN UPAYA HUKUM DAN EKSEKUSI PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) - Putra, I Putu Iwan Kharisma; Wiryawan, I Wayan; Rudy, Dewa Gde (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 01, Januari 2013, 2013)
In an era of economic development encountered various goods and or servicesare marketed to consumers. In trade practices that harm consumers, such as thedetermination of prices of goods and the use of improperly eksonerasi clause, thegovernment had consistently sided with consumers. Thus the need for regulationto protect consumers, in the act number 8 of 1999 on the protection ofconsumers. Setting the remedy with respect to any decision of the agency’sconsumer dispute resolution which is contradictory and inconsistent in actnumber 8 of 1999 on the protection of consumers.